Is oral nutritional therapy effective for the treatment of chylothorax? A case report - Machado, Juliana Deh Carvalho [UNESP]; Suen, Vivian Miguel Marques; Marchini, Julio Sergio (Elsevier B.V., 2008)
We report a case of a female patient who underwent corrective aortic coarctation surgery that progressed to chylothorax on the fifth postoperative day. Because the patient was clinically stable and had a functioning digestive tract, the nutritional team decided to treat her by oral nutritional support with a low-lipid diet, rich in medium-chain triacylglycerols. After 20 d, the patient returned to her habitual home diet and did not develop pleural spilling, showing full healing of the thoracic duct. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: chylothorax; nutritional therapy; medium-chain triacylglycerols